2019
DOI: 10.3390/microorganisms7110526
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance of Ammonia Oxidizing Archaea and Bacteria Influences Soil Nitrification Responses to Temperature

Abstract: Ammonia oxidizing archaea (AOA) and bacteria (AOB) are thought to contribute differently to soil nitrification, yet the extent to which their relative abundances influence the temperature response of nitrification is poorly understood. Here, we investigated the impact of different AOA to AOB ratios on soil nitrification potential (NP) across a temperature gradient from 4 °C to 40 °C in twenty different organic and inorganic fertilized soils. The temperature responses of different relative abundance of ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, many previous studies suggested that their relative abundances vary from fractional to several orders of magnitude, depending upon a variety of environmental factors—such as pH, salinity, organic carbon, temperature, ammonium and moisture content [ 5 , 6 , 7 , 8 , 9 , 10 ]. For instance, AOA dominates nitrification in low ammonium, low pH, and high temperature environments, while AOB dominates nitrification in high ammonium and low temperature environments [ 5 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many previous studies suggested that their relative abundances vary from fractional to several orders of magnitude, depending upon a variety of environmental factors—such as pH, salinity, organic carbon, temperature, ammonium and moisture content [ 5 , 6 , 7 , 8 , 9 , 10 ]. For instance, AOA dominates nitrification in low ammonium, low pH, and high temperature environments, while AOB dominates nitrification in high ammonium and low temperature environments [ 5 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assignment of selected T‐RFs to a various microbial genera with TRiFLe software revealed the presence of some ecologically important microorganisms. Among archaea, members of Nitrososphaera genus are ammonia oxidizing archaea (AOA) which are thought to be a key element in the nitrogen biogeochemical cycle (Mukhtar et al, 2019), Ferroplasma spp. species are involved in iron cycling (Golyshina, 2011) and representatives of Methanocaldococcus spp., Methanosaeta spp., Methanosarcina spp ., and Methanomethylovorans spp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ouyang et al 56 found that AOA in soils had an optimal temperature that was 10 °C higher than AOB. Mukhtar et al 57 reported that soils with higher AOA to AOB ratios had higher temperature optima for nitrification. With higher AOA to AOB ratios in the GoM compared to NE marshes, we would predict higher rates at the warmer temperatures in the GoM.…”
Section: Discussionmentioning
confidence: 99%